Clinico-epidemiological study of facial dermatoses among adolescents - Hemalingaiah, Manjunatha; Chekuri, Raghuveer; ., Veeresh (International Journal of Research in Dermatology, 2019)
Background: The obsession of getting a flawless skin is more for adolescents than in any other age group. But these problems are seldom given enough importance. Very common problem like acne vulgaris can cause serious psychological impact in them. Methods: Four hundred consecutive adolescent (10-19 years) patients with facial dermatoses presenting to skin department, VIMS, Ballari were selected for the study. Study design was descriptional and cross sectional, conducted from January 2013 to December 2013. Results: Eighty seven percentage of the study population was students and the rest were either labourers or drivers. Acne vulgaris was the diagnosis in 304 (76%) of cases. Second most common condition was seborrheic dermatitis accounting for 24 (6%) of cases. Conclusions: Facial dermatoses are common among the adolescents. These dermatoses are of a major cosmetic concern in this age group. Early diagnosis and proper management with education of patients is important to prevent late disfiguring complications and psychological sequelae.